Chitosan-Based Functional Materials for Skin Wound Repair: Mechanisms and Applications - Feng, Peipei; Luo, Yang; Ke, Chunhai; Qiu, Haofeng; Wang, Wei; Zhu, Yabin; Hou, Ruixia; Xu, Long; Wu, Songze (Frontiers in Bioengineering and Biotechnology, 2021)
Skin wounds not only cause physical pain for patients but also are an economic burden for society. It is necessary to seek out an efficient approach to promote skin repair. Hydrogels are considered effective wound dressings. They possess many unique properties like biocompatibility, biodegradability, high water uptake and retention etc., so that they are promising candidate materials for wound healing. Chitosan is a polymeric biomaterial obtained by the deacetylation of chitin. With the properties of easy acquisition, antibacterial and hemostatic activity, and the ability to promote skin regeneration, hydrogel-like functional wound dressings (represented by chitosan and its derivatives) have received extensive attentions for their effectiveness and mechanisms in promoting skin wound repair. In this review, we extensively discussed the mechanisms with which chitosan-based functional materials promote hemostasis, anti-inflammation, proliferation of granulation in wound repair. We also provided the latest information about the applications of such materials in wound treatment. In addition, we summarized the methods to enhance the advantages and maintain the intrinsic nature of chitosan via incorporating other chemical components, active biomolecules and other substances into the hydrogels.